Clinical and Radiological Follow-up of Intraneural Perineuriomas - Wilson, Thomas J; Amrami, Kimberly K; Howe, B Matthew; Spinner, Robert J (Neurosurgery, 2019)
ABSTRACT BACKGROUND Management of intraneural perineuriomas remains controversial, largely due to the lack of knowledge regarding the natural history of these lesions. OBJECTIVE To describe the typical radiological growth pattern of intraneural perineuriomas and to determine how the pattern of growth relates to clinical progression. METHODS We performed a retrospective review of the magnetic resonance imaging (MRI) studies and serial clinical examinations of a cohort of patients with biopsy-proven intraneural perineuriomas who had 2 MRI studies at least 2 yr apart. The outcome of interest was radiological growth in length or width of the intraneural perineurioma. Radiological growth was tested for association with clinical progression. RESULTS Twenty patients were included in the study. By width, the lesions were on average larger on repeat imaging (P = .009). By absolute length, the lesions were on average longer on repeat imaging (P = .02). By lesion:landmark ratio, there was no difference in length of the lesions between sequential images (P = .09), with 10 (50%) lesions being shorter and 7 (35%) showing no change. No lesions grew to involve a new nerve or division of a nerve on sequential imaging. None of the variables tested were associated with clinical progression. CONCLUSION We found that intraneural perineuriomas only rarely grow in length, do not grow to involve new nerves or nerve divisions, and growth does not correlate with clinical progression. These findings have significant ramifications for management of these tumors.